2014
DOI: 10.1002/psc.2603
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptide octarphin (TPLVTLFK), a selective agonist of nonopioidβ-endorphin receptor, stimulates nitric oxide synthesis in macrophages

Abstract: Synthetic peptide octarphin (TPLVTLFK, a selective agonist of nonopioid β-endorphin receptor) was able to activate in a dose-dependent manner murine macrophages to express nitric oxide (NO) synthase and to produce NO. Octarphin required lipopolysacharide for the optimal induction of NO production. Octarphin-dependent NO production was sensitive to inhibition by dexamethasone and the NO synthase specific inhibitor NG-monomethyl-L-arginine. In the concentration range of 1-1000 nM, octarphin increased the cyclic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…It was shown that, in the concentration range of 1-1000 nM, the peptide increases the activity of NOS and the content of NO and cGMP in LPS-activated murine peritoneal macrophages and human T lymphocytes. The activity of octarphin depended on dose and was maximal at a concentration of 100 nM [22,23].…”
Section: Action Of β-Endorphin and Peptide Tplvtlfk On Immunocompetenmentioning
confidence: 99%
“…It was shown that, in the concentration range of 1-1000 nM, the peptide increases the activity of NOS and the content of NO and cGMP in LPS-activated murine peritoneal macrophages and human T lymphocytes. The activity of octarphin depended on dose and was maximal at a concentration of 100 nM [22,23].…”
Section: Action Of β-Endorphin and Peptide Tplvtlfk On Immunocompetenmentioning
confidence: 99%